2009
DOI: 10.1007/s10495-009-0341-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to endoplasmic reticulum stress and apoptosis

Abstract: The endoplasmic reticulum (ER) is the cell organelle where secretory and membrane proteins are synthesized and folded. Correctly folded proteins exit the ER and are transported to the Golgi and other destinations within the cell, but proteins that fail to fold properly-misfolded proteins-are retained in the ER and their accumulation may constitute a form of stress to the cell-ER stress. Several signaling pathways, collectively known as unfolded protein response (UPR), have evolved to detect the accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
236
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(253 citation statements)
references
References 167 publications
11
236
0
6
Order By: Relevance
“…ER stress induces adaptive cell signaling known as unfolded protein response, as a result of which ERlocalized chaperones and proteins implicated in the ER-associated degradation pathway are induced. However, if the ER stress cannot be alleviated, it culminates into apoptosis (73,74). In this study, we found that although both wild type and str4 deletion strains have similar basal unfolded protein responses in normal and under ER stress conditions, induction of unfolded protein response was not observed in the presence of AdoHcy and homocysteine in the deletion mutant, suggesting that apoptosis under these conditions might not be mediated through ER stress.…”
Section: Discussionmentioning
confidence: 61%
“…ER stress induces adaptive cell signaling known as unfolded protein response, as a result of which ERlocalized chaperones and proteins implicated in the ER-associated degradation pathway are induced. However, if the ER stress cannot be alleviated, it culminates into apoptosis (73,74). In this study, we found that although both wild type and str4 deletion strains have similar basal unfolded protein responses in normal and under ER stress conditions, induction of unfolded protein response was not observed in the presence of AdoHcy and homocysteine in the deletion mutant, suggesting that apoptosis under these conditions might not be mediated through ER stress.…”
Section: Discussionmentioning
confidence: 61%
“…Under ER stress conditions, cells attempt to recover by inducing the expression of the UPR, known as the ER stress response. The UPR utilizes three types of ER-resident sensor proteins, IRE1, PERK and ATF6, that are activated by Bip (Larner et al, 2006;Lai et al, 2007;Rasheva and Domingos, 2009). The protein chaperone Bip/GRP78 is the major regulator of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bip is released from IRE1 and permitted to dimerize, which activates its kinase and RNase activities to initiate XBP-1 mRNA splicing, thereby producing a potent transcriptional activator (Back et al, 2006). Finally, Bip released from ATF6 permits ATF6 transport to the Golgi compartment where it is cleaved to yield a cytosolic fragment that migrates to the nucleus to further activate the transcription of UPR-responsive genes (Haze et al, 1999;Rasheva and Domingos, 2009;Shen et al, 2004). CHOP is a non-ER-localized transcription factor that is induced by ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial pathway can be initiated via intracellular damage or stress signals resulting in the release of cytochrome c from the mitochondria into the cytosol, apoptosome formation, and caspase-9 activation 47) . The endoplasmic reticulum (ER) stress pathway can be initiated by an accumulation of mis-folded and/ or unfolded proteins in the ER that can lead to ER stress, Ca 2+ release, calpain activation, and subsequent caspase-12 and caspase-9 activation 48) .…”
Section: Intracellular Ca 2+ and Muscle Damagementioning
confidence: 99%